KINERJA REKSADANA SYARIAH DENGAN METODE TREYNOR AND BLACK MODEL - Teguh Purwanto (FEB Universitas Muhammadiyah Pekajangan Pekalongan, 2017)
The purpose of this study was to evaluate the performance of Islamic mutual funds in Indonesia by using measuring Treynor and blacks models, the object of this research is an active Islamic mutual funds from November 2012 to October 2014 and Islamic mutual funds are categorized in this study amounted to 19 in research that 12 of the 19 Islamic mutual funds have a positive ratio means Islamic mutual funds are able to generate returns that correspond to specific risks and suitable as an investment, ranking the top three Islamic mutual funds are each Shariah index mutual funds, mutual funds mixture sharia, and sharia mutual revenue fixed. This study also found that Islamic mutual funds had an average return above average return Jakarta Islamic sharia reksadana risk index but worse than Jakarta Islamic index. and based on the rating in view of his return equity funds ranked first followed by mixed funds in second place and Islamic mutual funds index ranked the three